The deconstruction and reconstruction of sports coaching: An interview with Professor Robyn Jones - Jenkins, S. (International Journal of Sports Science & Coaching, 2017)
Robyn Jones is arguably the world's leading researcher and scholar in the microsociology of sports coaching. Viewing coaching as a 'complex socio-pedagogical process' he has drawn especially from Erving Goffman's work on stigma, interaction and impression management, in addition to educational perspectives such as Nel Noddings' feminist ethic of care. This article and the accompanying commentaries from Robyn's current and past doctoral students, as well as some colleagues from academia, is focused on the ontology, epistemology and methodology of research in sports coaching. ABSTRACT FROM AUTHOR